Technical Advice For Students Interested In Poultry Subjects At The Animal Science Faculty - University Of Nusa Cendana - Ni Gusti Ayu Mulyantini; Ni Putu Febri Suryatni (Jurnal Pengabdian Masyarakat, 2026)
Purpose: To enhance poultry science students’ research independence and data validity by addressing practical training gaps in animal science education, ultimately strengthening methodological rigor in poultry research. Method: Fifteen Animal Science students from Universitas Nusa Cendana participated in a structured program integrating theoretical lectures, simulation demonstrations, and hands-on practice in experimental poultry facilities to evaluate competency development. Practical Applications: Improved technical proficiency enables reliable experimental data collection for poultry nutrition and production studies, directly supporting agricultural research, farm management optimization, and evidence-based industry practices. Conclusion: The training significantly increased research independence, methodological understanding, and experimental discipline, providing an effective educational strategy to advance accuracy and innovation in poultry science.